Réponses

2013-12-27T00:43:39+01:00
A= (4x-3)² - (4x-3) (3-9x)
1. développer et réduire
A= 16x² -24x +9 -( 12x - 36x²- 9 + 27x)
A= 52 x² - 63 x +18
2. factoriser
A= (4x-3)² - (4x-3) (3-9x)
A = (4x-3) (4x-3 -3+9x)
A = (4x-3) ( 13 x - 6)
3. calculer A pour x=2
 (4x-3) ( 13 x - 6)=
8-3 * (26-6)=
5*20=
A= 100 pour x=2 

4. factoriser B=(7x-3)² - 9
B= (7x-3)² - 3²
B= (7x-3-3) ( 7x-3+3)
B= (7x-6)  7x


2013-12-27T01:26:13+01:00
1)  ( 4 x -3)²      - (4x-3) (3-9x)
 (4x)²-2*4x*3+3²) - (4x-3)*(4x-9x)*((-3)+3)*(-3-9x)
 (16x²-24x+9)    -   (4x-3)*(-5x)*((-3+3)*(-3-9x)
                             4x*(-5x)*(-9x)=180³
                              -3+3*-3= -3+(-9)=-12
(16x²-24x+9) - (180x³ -12)
16x²-24x+9-12- 180x³
16x²-24x-21-180x³

2)
 A= (4x-3)² - (4x-3) (3-9x)
A = (4x-3) (4x-3 -3+9x)
A = (4x-3) ( 13 x - 6)


3) (4x2 -3)² - (4x2-3) (3-9x2)
      (8-3)²   - (8-3)    (3-18)
        25     - 5  *    (15)
        25-(-75)=100
4)
A = (7x - 3)  - 9
   =
(7x - 3) x (7x - 3) - 3 x 3
   =
[(7x - 3) + 3] x [(7x - 3) - 3]
    [(7x - 3) + 3] = [7x - 3 + 3] = (7x)
    [(7
x - 3) - 3] = [7x - 3 - 3]= (7x - 6)
   
A = 7x (7x - 6)